2018
DOI: 10.1080/13501763.2018.1531912
|View full text |Cite
|
Sign up to set email alerts
|

Trusting nudges? Lessons from an international survey

Abstract: In the past decade, policymakers have increasingly used behaviourally informed policies, including 'nudges,' to produce desirable social outcomes. But do people actually endorse those policies? This study reports on nationally representative surveys in five countries (Belgium, Denmark, Germany, South Korea, and the US) carried out in 2017/2018. We investigate whether people in these countries approve of a list of 15 nudges regarding health, the environment, and safety issues. A particular focus is whether trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 41 publications
9
92
2
4
Order By: Relevance
“…Of the German consumers, 63.4% support nutrition policy in general, 11.2% have a negative attitude and 25.4% are indifferent (Appendix A Table A1). These findings are in line with the literature [42,70,71]. The assessment of concrete instruments gives a more complex picture and shows approval ratings of between 34.2% and 78.7% depending on the instrument (50.9% on the average of all instruments, Appendix A Table A2).…”
Section: Discussionsupporting
confidence: 90%
“…Of the German consumers, 63.4% support nutrition policy in general, 11.2% have a negative attitude and 25.4% are indifferent (Appendix A Table A1). These findings are in line with the literature [42,70,71]. The assessment of concrete instruments gives a more complex picture and shows approval ratings of between 34.2% and 78.7% depending on the instrument (50.9% on the average of all instruments, Appendix A Table A2).…”
Section: Discussionsupporting
confidence: 90%
“…This finding seems to be consistent among both my own studies (paper 1-4) but also with other studies conducted since 2016 (e.g. Jung and Mellers, 2016;Reisch, Sunstein and Gwozdz, 2017;Sunstein, 2016a;Sunstein, 2017a;Sunstein, Reisch and Rauber, 2017;Loibl et al, 2018;Sunstein et al, 2018). There is, however, variance regarding when people find nudges acceptable.…”
Section: Discussionsupporting
confidence: 91%
“…Acceptance and the choice architect Dolan et al 2012 also argue that is the messenger's identity and your relation to the messenger matters a lot for the effectiveness of the nudge. In accordance with this argument, Sunstein, et al, (2018) have shown that trust in public institutions are an important factor for accepting nudges. This is also consistent with the "nudge partisan bias" which has been found by Tannenbaum et al (2017).…”
Section: Adding Alternatives To the Modelmentioning
confidence: 54%
“…This research extends previous studies (Sunstein, 2015(Sunstein, , 2016a(Sunstein, , 2016bSunstein, Reisch, & Kaiser, 2018;Sunstein, Reisch, & Rauber, 2018) to determine Koreans' unique perspectives on behavioral economics concepts, particularly in terms of gender differences that are manifest in preference for progressive policies. Gender issues, particularly in terms of the conflict between traditional Korean roles and modern responsibilities, are particularly worthwhile for study in the nascent behaviorally informed policy field for Korea as the biases are being challenged from all sides.…”
Section: Introductionsupporting
confidence: 69%